Fibroma of tendon sheath. Issue 8 (August 1982) - Smith, P S; Pieterse, A S; McClure, J
Abstract : A series of nine cases of fibroma of tendon sheath is described including details of the ultrastructural features of two cases. The series was composed of lesions from six males and three females with a mean age of 38 yr. The most common site of involvement was the hand (including fingers) and the mean greater diameter was 19 mm. Typically the tumours were lobulated and microscopically there was a collagenous stroma with spindle and stellate cells in a moderate degree of cellularity. One recurrence was noted in the series. The lesion was distinguished from circumscribed fibromatosis, nodular fasciitis, neurofibroma, leiomyoma, scar tissue, giant cell tumour of tendon sheath (localised nodular tenosynovitis) and fibrous histiocytoma. Ultrastructural studies revealed that the large majority of cells present in the two cases studied were myofibroblasts and fibroma of tendon sheath is therefore the third instance of a benign tumour containing these cells (the other two being dermatofibroma and giant cell fibroma of the oral mucosa).